Do Multinationals Transplant Their Business Model? - Dalia Marin; Linda Rousova; Thierry Verdier (Center for Economic Studies and ifo Institute (CESifo), 2019)
What determines whether or not multinational firms transplant the mode of organisation to other countries? We embed the theory of knowledge hierarchies in an industry equilibrium model of monopolistic competition to examine how the economic environment may affect the decision of multinational firms about transplanting the mode of organization to other countries. We test the theory with original and matched parent and affiliate data on the level of decentralization of 660 Austrian and German multinational firms and 2200 of their affiliate firms in Eastern Europe. We find that three factors stand out in promoting the multinational firm's decision to transplant the organisational form to the affiliate firm in the host country: a competitive host market, the human resource policy of the multinational firm, and when an innovative technology is transferred to the host country. These factors increase the respective probabilities of organizational transfer by 7, 21, and 24 percentage points.
Keywords: D23; F12; F23; F61; 330; organizational economics of multinational firms; trade and organisation; the theory of the firm; organizational transfer between countries